Continuous quadratus lumborum block as part of multimodal analgesia after total hip arthroplasty: a case report - Bak, Hahyeon (Korean J Anesthesiol, 2020)
BACKGROUND: Commonly used epidural or systemic analgesics for pain control after hip surgery carry risk for potential adverse effects. In contrast, the quadratus lumborum block (QLB) utilizes a simple and easy fascial plane technique and provides a wide area of sensory blockade. Thus, the QLB may be beneficial as analgesia after total hip arthroplasty. CASE: Here, we report the case of an 83-year-old man who received a continuous transmuscular QLB as part of a multimodal analgesia after hardware removal and total hip arthroplasty. The patient received a continuous infusion of 0.2% ropivacaine at 8 ml/h through an indwelling catheter in addition to patient-controlled analgesia with intravenous fentanyl and oral celecoxib. The patient’s pain scores did not exceed 4, and no additional analgesics were required until postoperative day 5. CONCLUSIONS: Transmuscular QLB may be a suitable option for multimodal analgesia after total hip arthroplasty.